172k views
17 votes
Simplify :- a). { ( 3/5)-² ÷ (5/3)² } + 5/3

b) (x/y)-² × (x/y)⁴ × (x/y)-¹

pls help me else u won't get 100 points ......

give me correct answer else I will report u
this question is related to the grade 8 exponent and power ​

2 Answers

4 votes

Answer:


(a) \: \underline{\boxed{ ans = (5)/(3)}} \\ (b) \: \underline{ \boxed{ans = (x)/(y) }}

Explanation:


if \: the \: question \: is \to simplify \\ a).......... { ( (3)/(5))^( - 2) ÷ ((5)/(3))^(2) } + (5)/(3) \\ \\ b)....( (x)/(y))^( - 2) × ( (x)/(y))^( 4) × ( (x)/(y))^( - 1) \\ \\ \underline{ \boxed{solution....(a)}} \\ \\ ((3)/(5) )^( - 2) / \: ((3)/(5) )^( 2) + (5)/(3) = \\ \\ (1)/(((3)/(5))^(2)) / \: ((3)/(5) )^( 2) + (5)/(3) = \\ \\ ((5)/(3) )^( 2) / \: ((3)/(5) )^( 2) + (5)/(3) = \\ \\ ((3)/(5) )^( 2) * ((5)/(3) )^( 2) + (5)/(3) = \\ \\ (9 * 25)/(25 * 9) + (5)/(3) = 1 + (5)/(3) \\ \underline{\boxed{ ans = (5)/(3)}} \\ \\ \underline{ \boxed{solution....(b)}} \\ \\ ( (x)/(y))^( - 2) × ( (x)/(y))^( 4) × ( (y)/(x))^( - 1) = \\ \\ ( (x)/(y))^( - 2) × ( (x)/(y))^( 4) × ( (x)/(y))^( - 1) \\ since \: the \: two \: bases \: are \: same \to \\ ( (x)/(y))^( - 2) ×( (x)/(y))^((4 + ( - 1)) = \\ \\ ( (y)/(x))^(2) ×( (x)/(y))^(3) = \frac{ {y}^(2) * {x}^(3) }{ {x}^(2) * {y}^(3) } = (x)/(y) \\ \\ \underline{ \boxed{ans = (x)/(y) }}

User Imjohsep
by
4.9k points
3 votes

Answer:

  1. A is most likely 8/5 and B is most likely x/y sorry if this does not help.

User Andrea Carron
by
5.1k points